Pharmacokinetics and safety of rucaparib in patients with advanced solid tumors and hepatic impairment - Grechko, Nikolay; Skarbova, Viera; Tomaszewska-Kiecana, Monika; Ramlau, Rodryg; Centkowski, Piotr; Drew, Yvette; Dziadziuszko, Rafal; Zemanova, Milada; Beltman, Jeri; Nash, Eileen; Habeck, Jenn; Liao, Mingxiang; et al. (Cancer chemotherapy and pharmacology, 2021)
PURPOSE: The poly(ADP-ribose) polymerase inhibitor rucaparib is approved for the treatment of patients with recurrent ovarian and metastatic castration-resistant prostate cancer; however, limited data are available on its use in patients with hepatic dysfunction. This study investigated whether hepatic impairment affects the pharmacokinetics, safety, and tolerability of rucaparib in patients with advanced solid tumors. METHODS: Patients with normal hepatic function or moderate hepatic impairment according to the National Cancer Institute Organ Dysfunction Working Group (NCI-ODWG) criteria were enrolled and received a single oral dose of rucaparib 600 mg. Concentrations of rucaparib and its metabolite M324 in plasma and urine were measured. Pharmacokinetic parameters were compared between hepatic function groups, and safety and tolerability were assessed. RESULTS: Sixteen patients were enrolled (n = 8 per group). Rucaparib maximum concentration (Cmax) was similar, while the area under the concentration-time curve from time 0 to infinity (AUC0-inf) was mildly higher in the moderate hepatic impairment group than in the normal control group (geometric mean ratio, 1.446 [90% CI 0.668-3.131]); similar trends were observed for M324. Eight (50%) patients experienced ≥ 1 treatment-emergent adverse event (TEAE); 2 had normal hepatic function and 6 had moderate hepatic impairment. CONCLUSION: Patients with moderate hepatic impairment showed mildly increased AUC0-inf for rucaparib compared to patients with normal hepatic function. Although more patients with moderate hepatic impairment experienced TEAEs, only 2 TEAEs were considered treatment related. These results suggest no starting dose adjustment is necessary for patients with moderate hepatic impairment; however, close safety monitoring is warranted.
Keywords: játra; indoly; Humans; Indoles; lidé středního věku; Liver Diseases; Liver Function Tests; Female; jaterní testy; Aged; dospělí; Antineoplastic Agents; Area Under Curve; Rucaparib; Poly(ADP-ribose) polymerase inhibitors; senioři; lidé; PARP inhibitory; Hepatic impairment; Poly(ADP-ribose) Polymerase Inhibitors; Adult; nemoci jater; ženské pohlaví; Liver; Male; Middle Aged; Neoplasms; protinádorové látky; nádory; plocha pod křivkou; Safety; Pharmacokinetics; mužské pohlaví